The Kyrgyz Republic : Poverty Update, 2011 - World Bank (Washington, DC, 2013)
This report aims to provide an update of the profile of the poor and describe the dynamics of poverty and inequality in the Kyrgyz Republic during 2007-2011. This period was marked by economic and political volatility which adversely impacted the country's capacity to achieve some of the Millennium Development Goals (MDG). The lack of progress in indicators related to maternal and child health and combating HIV/AIDS and other diseases continues to be of concern. However, in comparison to other low-income countries, non-monetary indicators of poverty in the Kyrgyz Republic fare relatively well in such areas as health, education, and access to basic infrastructure services. The report finds that at the micro-level the leading factors associated with poverty are household demographic characteristics. Larger and younger households with relatively fewer income-generating members and more net consumers, such as children, are more prone to poverty. Female-headed households have lower consumption per capita all other things held equal.